The Fertility Response to Cutting Child-Related Welfare Benefits - Malte Sandner; Frederik Wiynck (Population Research and Policy Review, 2023)
Despite long-term interest in whether welfare benefits motivate fertility, evidence from research has not been consistent. This paper contributes new evidence to this debate by investigating the fertility effect of a German welfare reform. The reform decreased the household income of families on welfare by 18% in the first year after the birth of a baby. Using exclusive access to German social security data on over 460,000 affected women, our analysis finds that the reform leads to a fertility reduction of 6.8%. This result implies that for mothers on welfare, fertility has an income elasticity of 0.38, which is much smaller than that of general populations reported in the literature. Our findings suggest that welfare recipients' fertility reacts less strongly to financial incentives than the fertility of overall populations.
Keywords: J13; I38; C54; 300; Welfare benefits; Fertility; Parental leave benefits